Study Of Most Affected Age Group of Anemia Among Pregnant Women Attending At El-Nuhud Teaching Hospital, West Kordufan State, 2019. - Balla Altaeb Ahmed Alnour; Dr: Gabr Alla Hamad (Journal of Medical Care Research and Review, 2024)
Background: Anemia is a common problem in Africa, with prevalence ranging from 21.1% to 64.4%. According to WHO estimates, 56 million pregnant women were anemic in 2005, more than half of them (57.6%) would be in Africa. Objectives: The main objective of this study to determine the most affected age group of anemia among pregnant women attending at El-Nuhud Teaching Hospital, West Kordufan State, 2019. Methodology: A cross-sectional descriptive hospital based study was carried out from August to November 2019. The sample size was total coverage of all pregnant women attending at El-Nuhud Teaching Hospital, West Kordufan State. A number of 420 samples of data of structured administrated questionnaire and blood samples were collected from pregnant women. The blood samples were collected and investigated by laboratory technician by using Colorimeter to measure hemoglobin level. The data were analyzed by using Statistical Package for Social Science (SPSS), version 20and Chi-Square test (X2) used to check difference between variables, p value less than 0.05 was considered significant. Results: The results indicated the high affected in illiteracy (77.6%) followed by primary (57.1%), Khalwa (50%), secondary (42.8%), university (26.7%) and post university (0%).This significant relation between educational level for pregnant woman and anemia among pregnant women, (p value = 0.000).. Conclusion: The study concluded that the prevalence of anemia among pregnant women was more than half. The study recommended to implement health education programmes at all levels, use appropriate vaccinations, supplementations and vitamins during pregnancy to prevent anemia, family planning, optimum maternal and child health, and environmental Sanitation.